ANALISIS PENDAPATAN DAN EFISIENSI TEKNIS USAHATANI JAGUNG DI KECAMATAN BANDAR SRIBHAWONO KABUPATEN LAMPUNG TIMUR - Titiana, Asih; Murniati, Ktut; Kasymir, Eka (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
The purpose of this research is to analyze the income and technical efficiency of corn farming. The study was conducted in Bandar Sribhawono Subdistrict East Lampung Regency from January to March 2020. The study involved farmers and traders as participants. In this study, 45 respondents from farmer groups were chosen using a straightforward random procedure. The data utilized were primary and secondary data. The data analysis method employed income analysis and linear programming. The findings indicate that corn farming in Bandar Sribhawono Subdistrict is feasible and economical, with R/C values greater than one. Technically, corn farming efficiently utilizes its production elements.Keywords: corn, efficiency, income